A schoolwide approach to promoting student bystander behavior in response to the use of the word "retard". (September 2018) - Siperstein, Gary N.; Albert, Avery B.; Jacobs, Holly E.; Osborne, Karen J.; Stokes, Jeffrey E.
Highlights: Students often use the r-word as an insult or joke toward their peers. Students are more likely to intervene when they hear the r-word used as an insult. Students do not understand the r-word is harmful even when not used as an insult. Participation in a schoolwide inclusion program promotes bystander behavior. School-based interventions are promising for addressing the r-word and stigma. Abstract: Background and aims: The use of the word retard ("the r-word") among adolescents sheds light on societal views about individuals with intellectual disability and the need to address the colloquial use of this word and its underlying stigma. Schools provide an important platform for intervening to promote social change among youth. The present study examined the impact of a schoolwide social inclusion program on students' bystander behavior against the use of the r-word. Methods and procedures: 1233 students from 5 high schools were surveyed about the prevalence of the r-word in their school, the contexts in which it is used, and their bystander behavior in response to the word. Approximately 40% of surveyed students participated in an R-word Campaign, Unified Sports team, and/or Unified Club as part of the Special Olympics Unified Champion Schools (UCS) program. Outcomes and results: Students' prosocialness, the context in which the r-word was used, and participation in UCS activities significantly predicted active bystander behavior in response to the r-word. Conclusions and implications: By empowering students to be active bystanders against the use of the r-word in school, school-based interventions provide a promising avenue for addressing both the use of the r-word and its underlying stigma.